Fraud in the 2018 Egyptian presidential election?. Issue 1 (1st January 2021) - Ketchley, Neil
ABSTRACT: This research note scrutinizes official vote counts from the 2018 Egyptian presidential election. Drawing on data for 13, 807 polling stations published by the Egyptian Electoral Authority, it uses the Election Forensics Toolkit to estimate a series of digit and distribution tests. The results point to statistical anomalies in voter turnout for polling stations located in Egypt's major population centres. The findings align with journalistic accounts of very low turnout in those areas and demonstrate how tools from electoral forensics can be applied to the study of elections in the Middle East and North Africa.